Community-Based Participatory Research Helps Farmers and Scientists to Manage Invasive Pests in the Ecuadorian Andes - Dangles, O. (Springer Netherlands, 2010)
Participatory research has not been a conspicuous methodology in developing nations for studying invasive pests, an increasing threat to the sustainable development in the tropics. Our study presents a community-based monitoring system that focuses on three invasive potato tuber moth species (PTM). The monitoring was developed and implemented by young farmers in a remote mountainous area of Ecuador. Local participants collected data from the PTM invasion front, which revealed clear connection between the abundance of one of the species (Tecia solanivora) and the remoteness to the main market place. This suggests that mechanisms structuring invasive populations at the invasion front are different from those occurring in areas invaded for longer period. Participatory monitoring with local people may serve as a cost-effective early warning system to detect and control incipient invasive pest species in countries where the daily management of biological resources is largely in the hands of poor rural people.